A Plasmodium‐like virulence effector of the soybean cyst nematode suppresses plant innate immunity. Issue 2 (6th June 2016) - Noon, Jason B.; Qi, Mingsheng; Sill, Danielle N.; Muppirala, Usha; Eves‐van den Akker, Sebastian; Maier, Thomas R.; Dobbs, Drena; Mitchum, Melissa G.; Hewezi, Tarek; Baum, Thomas J.
Summary: Heterodera glycines, the soybean cyst nematode, delivers effector proteins into soybean roots to initiate and maintain an obligate parasitic relationship. HgGLAND18 encodes a candidate H. glycines effector and is expressed throughout the infection process. We used a combination of molecular, genetic, bioinformatic and phylogenetic analyses to determine the role of HgGLAND18 during H. glycines infection. HgGLAND18 is necessary for pathogenicity in compatible interactions with soybean. The encoded effector strongly suppresses both basal and hypersensitive cell death innate immune responses, and immunosuppression requires the presence and coordination between multiple protein domains. The N‐terminal domain in HgGLAND18 contains unique sequence similarity to domains of an immunosuppressive effector of Plasmodium spp., the malaria parasites. The Plasmodium effector domains functionally complement the loss of the N‐terminal domain from HgGLAND18. In‐depth sequence searches and phylogenetic analyses demonstrate convergent evolution between effectors from divergent parasites of plants and animals as the cause of sequence and functional similarity. Abstract : See also the Commentary on this article by Betz et al. 212: 306–309 .